Zmiany krajobrazu województwa wielkopolskiego od początku transformacji ustrojowej - Łowicki, Damian (My University, 2015)
The increasing conviction of scientific circles and governments of states that it is necessary to protect the environment not only through active or passive protection of its individual components but, above all, through managing the environment as a whole, resulted in a growing interest in the landscape observed in recent years. Effective environmental protection requires considering not only the bilateral influence between a particular factor and the object studied but also the mutual influence of factors on one another. The landscape, which is an effect of the interaction between the components of the environment and constitutes the physiognomic layer of ecosystems, makes it possible to perform such actions. This conclusion is based, among other things, on the results of ecological studies – which led to the formulation of one of the paradigms of landscape ecology, according to which landscape structure determines its functions – and the description of the significance of various characteristics of landscape compositions and configurations to its functioning. The issue of landscape changes is especially important in the case of a study area such as the voivodeship of Wielkopolska. In comparison to other voivodeships, Wielkopolska underwent more rapid changes. The studies carried out within the CORINE Land Cover programme for the years 1990-2000 show that this voivodeship tops the list as regards the surface area of land cover changes. Those changes clearly lead to landscape anthropogenisation. The system transformation and opening of borders to the West created very favourable conditions for the central Wielkopolska because of its attractive location on the Berlin-Warsaw route. Poznań, along with Wrocław, became a Polish urban centre that were closest to Western Europe. Rapid economic growth overlapped with the historical agricultural structure, which had to entail significant changes in land use and consequently further landscape changes. This monograph presents the results of the author’s research in landscape changes in the voivodeship of Wielkopolska. The results include a quantitative analysis of the changes in the share of individual landscape elements in Wielkopolska between 1989 and 2005 and identification of those which had the largest impact on landscape change. Assuming that land use is a result of the interaction between human activity and natural conditions, the author characterised all communes of the voivodeship by assigning socio-economic and natural profiles to them. The identification of the proportion of those two types of influence and the observation of the manner in which it changed in time and space bears a strong reference to the sustainable development principle. The relationbetween the speed of landscape changes, and the rate of changes in socio-economic factors and natural conditions permitted to identify the communes at risk of a clash of human activity and natural tendencies. It is particularly important to create insightful and xhaustive ecological studies encompassing the entire area of those communes and take them into account in the planning and programming processes. The research has confirmed that regardless of the decreasing scale of landscape changes after 1989, the diversity of this feature across the voivodeship is very significant and tends to grow. This phenomenon is in this paper referred to as the polarisation of changes and consists in a slower land change in communes where in 1989 the landscape was affected only to a small extent, and a faster change in communes where it was highly affected. The phenomenon causes a deepening landscape divergence across the subregions of the voivodeship. The increase in the diversity of land use changes in a regional perspective overlaps with the decrease on the level of the commune. This process may have very profound social, economic and, above all, ecological implications. Particularly if it occurs in areas where natural conditions are not in line with the direction of development. The largest diversity of pace is observable in the case of the surface area of forests and settlement areas. The results of this study show that it is the socio-economic factors that have the largest impact on land changes, not economic factors, which proved to be of minor importance. In the case of farmland, forests and settlement areas, the occurrence of protected drainages, watershed zones or sheet erosion risk were irrelevant to the spatial development of the region. High quality of the agricultural production space did not hinder urbanisation either but only limited the forest share increase. The results of the study conducted lead the author to the conclusion that the causative factors of the landscape change polarisation in Wielkopolska were differences in economic activity of its population. This conclusion allows to ascertain that efficient actions aiming at narrowing the disparities in the development level of different parts of the voivodeship require stimulating the human potential, i.e. education and business activity. Such actions would lead to a more rational use of space and the potential of the features inherent in the natural environment. Therefore, they should be emphasised in the regional programming documents, and in particular in the voivodeship development strategy. The current spatial planning system operative in Poland is not conducive to stopping the adverse development tendencies in Wielkopolska. The fundamental reasons for this are the weak legal status of the voivodeship spatial development plan and its inconsistency with other voivodeship programming documents.
Landscape changes of the voivodeship of Wielkopolska since the beginning of the political (and economic) transformation
Keywords: zmiany użytkowania ziemi; województwo wielkopolskie; transformacja ustrojowa; polaryzacja krajobrazu